2021
DOI: 10.3390/microorganisms9122548
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Age of Cecal Material Transfer Donors on Alzheimer’s Disease Pathology in 5xFAD Mice

Abstract: Alzheimer’s disease is a progressive neurodegenerative disorder affecting around 30 million patients worldwide. The predominant sporadic variant remains enigmatic as the underlying cause has still not been identified. Since efficient therapeutic treatments are still lacking, the microbiome and its manipulation have been considered as a new, innovative approach. 5xFAD Alzheimer’s disease model mice were subjected to one-time fecal material transfer after antibiotics-treatment using two types of inoculation: mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 94 publications
(112 reference statements)
1
15
0
Order By: Relevance
“…For example, increased levels of circulating LPS, the main component of the outer membrane in Gram-negative bacteria, have been identified in MCI and AD patients [ 383 ]. Indeed, LPS can induce the activation of pro-inflammatory pathways, promoting BBB disruption and neuroinflammation [ 384 , 385 ]. Furthermore, short-chain fatty acids (SCFAs), usually beneficial for their anti-inflammatory and antioxidant properties in the intestinal lumen, can be released in the blood upon dysbiosis, reach the cerebral circulation, and cause potentially harmful effects on brain function [ 383 , 386 , 387 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, increased levels of circulating LPS, the main component of the outer membrane in Gram-negative bacteria, have been identified in MCI and AD patients [ 383 ]. Indeed, LPS can induce the activation of pro-inflammatory pathways, promoting BBB disruption and neuroinflammation [ 384 , 385 ]. Furthermore, short-chain fatty acids (SCFAs), usually beneficial for their anti-inflammatory and antioxidant properties in the intestinal lumen, can be released in the blood upon dysbiosis, reach the cerebral circulation, and cause potentially harmful effects on brain function [ 383 , 386 , 387 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, neuronal loss in the CNS occurs at 3 months, and cognitive impairment is observed at 5 months of age 25,26 . Literature has reported that 5xFAD mice also present minor GI dysmotility, 22,27 changes in enteric neuronal structure, 27 altered colonic gene expressions and calcium homeostasis, increased enteric neuronal viability, 22 and GI dysbiosis 28 . However, there is no study directly supporting that Aβ accumulation occurs in enteric ganglia in the myenteric plexus of 5xFAD mice and if Aβ accumulation disrupts myenteric neuromuscular transmission causing GI dysmotility.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment was based on [1]. In our previous experiments conducted in Alzheimer's disease model mice [23], we observed an effective reduction in the gut microbiome by a similar antibiotics cocktail. Probiotics-treated animals received 10 9 CFU/mL (OptiBac for those on antibiotics, OptiBac Probiotics HQ Wren Laboratories Ltd., Hampshire, UK, contains L. acidophilus and L. rhamnosus), which resulted in elevated amounts of Lactobacillaceae in another mouse strain [23] and is in accordance with other published treatment approaches in rodents (for example, [24,25]).…”
Section: Chronic Social Stressmentioning
confidence: 94%
“…For males, collection of feces was conducted with euthanization (22 weeks of age). Fecal samples were analyzed at the MVZ Institut fuer Mikrooekologie GmbH (Herborn, Germany) as described before [23]. Standard curves were produced using the appropriate reference organism to quantify qPCR values into the number of bacteria per gram (wet weight).…”
Section: Qpcr For Quantitation Of Selected Bacteriamentioning
confidence: 99%